Interação pela linguagem na avaliação de produções escritas: ordem ou diálogo? - Albert, Silvia Augusta de Barros (2007)
The present Dissertation is part of the research area, Reading, Writing and Portuguese language Teaching and its theme is the interaction through language in evaluations of writing produced in Ensino Fundamental II (students aged 11-15), with the teaching and learning of writing as a perspective. The choice of theme is justified by the fact that the evaluation of writing is a disquieting presence in teaching practice. The aim of this study is to carry out a study of linguistic strategies of interaction and the markers of subjectivity in the teacher s evaluative feedbacks on student s writing. The study is based on the Theory of Enunciation (Kerbrat-Orecchioni 1991; 1997; 1998; 2001 e 2005); on the Theory of Speech Acts (Austin, 1990 e Searle, 1981 e 1995); and on approaches towards Pedagogy and the Pedagogy of Writing, especially on Perrenoud (1999 e 2002) e Plane (1994 e 1996). The hypothesis is that, even though the teacher intends to propose a dialogue, another action, in terms of order and judgment, is superimposed on this intention, and this can be seen in the linguistic strategies of interaction and by the markers of subjectivity. Hopefully, this study will open new perspectives for the teaching and learning of writing for new research in the area